Genomic expression assay testing among American Indian and Alaska Native women with breast cancer. Issue 24 (14th September 2020) - Marmor, Schelomo; Longacre, Colleen F.; Altman, Ariella M.; Hui, Jane Y. C.; Jensen, Eric H.; Tuttle, Todd M.
Abstract : Background: Breast cancer is one of the most common causes of cancer mortality for all women, including American Indian and Alaska Native (AI/AN) women. The use of the 21‐gene recurrence score (RS) appears to be predictive of the benefit of chemotherapy for women with estrogen receptor (ER)–positive breast cancer. The objective of the current study was to compare RS testing between AI/AN and non‐Hispanic White (NHW) women with breast cancer. Methods: The Surveillance, Epidemiology, and End Results program was used to identify women with ER‐positive breast cancer from 2004 through 2015. Multivariable logistic regression was used to evaluate factors associated with RS use, with high‐risk RS, and with chemotherapy use among those with a high‐risk RS. Results: A total of 363, 387 NHW patients and 1951 AI/AN patients with ER‐positive breast cancer were identified. AI/AN women were found to be less likely to undergo RS testing and, when tested, were more likely to have a high‐risk RS. In the multivariable logistic regression analysis, AI/AN women were found to be significantly more likely to have a high‐risk RS (odds ratio, 1.28; 95% confidence interval, 1.01‐1.66). Among untested women, chemotherapy use was higher for AI/AN women; however, the use of chemotherapy was not found to be significantly different between the groups with a high‐risk RS. Using Cox proportional hazards models, AI/AN race was found to be significantly associated with worse overall survival. Conclusions: AI/AN women were less likely to undergo RS testing compared with NHW women and were more likely to have a high‐risk RS. Reversing the disparity in genomic expression assay testing is critical to ensure guideline‐based breast cancer treatment and improve survival rates for AI/AN women with breast cancer. Abstract : Compared with non‐Hispanic White (NHW) women, American Indian and Alaska Native (AI/AN) women with estrogen receptor—positive breast cancer appear to be less likely to undergo genomic expression assay testing. Among tested women, AI/AN patients with breast cancer are more likely to have high‐risk recurrence scores compared with NHW women.